Cultures of America Korean Americans - Lee, Lauren (Marshall Cavendish Corporation, 1995)
An extensive study with well-chosen color photos of the culture of Korean Americans, with coverage of topics like religion and customs.
Keywords: Asian American; Juvenile Nonfiction; People & Places; United States